2019
DOI: 10.1016/j.ygyno.2019.03.247
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of a recurrent polymerase-epsilon (POLE)-mutated endometrial cancer

Abstract: POLE mutations occur in 7-12% of endometrial cancers and are identified by molecular analysis.• POLE-mutated endometrial cancers have high tumor mutation burden, tumor neoantigen production, and tumor infiltrating T cells.• This case illustrates a marked response to immune checkpoint inhibition in a POLE-mutated endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Previous results suggest that POLE mutational status was associated with tumor mutational burden in endometrial cancers [32] consistent with our finding (Fig. 1c).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Previous results suggest that POLE mutational status was associated with tumor mutational burden in endometrial cancers [32] consistent with our finding (Fig. 1c).…”
Section: Resultssupporting
confidence: 93%
“…Somatic mutations in POLE have been found in endometrial cancers in many studies. These reports include family studies that have confirmed the existence of novel POLE pathogenic germline variants and phenotypes of POLE-mutations in endometrial cancer (mutation analysis, clinical and lifestyle data, prognosis) [7, 32, 41, 42]. However, how do POLE mutations affect the prognosis of endometrial cancer?…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the amino acid changes underlying POLE mutations differed between the left‐ and right‐side colon. Currently, increasing research is focused on finding new markers for immunotherapy, and POLE gene mutations are considered a promising marker in various cancer types 18–20 . We advocate that more clinical trials should be focused on detecting POLE gene mutations to identify additional clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, increasing research is focused on finding new markers for immunotherapy, and POLE gene mutations are considered a promising marker in various cancer types. [18][19][20] We advocate that more clinical trials should be focused on detecting POLE gene mutations to identify additional clinical features. Here, we present an overview of the clinical patterns of patients with POLE mutations and report significant differences among diverse groups, which could contribute to identifying specific groups of patients who could benefit from immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The search strategy retrieved 72 articles. Overall, 18 reviews (21-38) and 8 case reports (39)(40)(41)(42)(43)(44)(45)(46) were identified, while 40 studies were deemed irrelevant. After removal of ineligible studies, 6 studies were recruited (47)(48)(49)(50)(51)(52).…”
Section: Data On Efficacy and Safetymentioning
confidence: 99%